Analisis Nilai Tambah Pengolahan Kopra di Desa Waepandan Kecamatan Kepala Madan Kabupaten Buru Selatan - Taipabu, La Idrus Farid; Saediman, Saediman; Fyka, Samsul Alam (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2018)
This study aims to determine the value added value obtained by farmers from copra processing. This research has been conducted in Waepandan Village, Madan District Head of South Buru Regency in March until May 2017. The determination of this research location is based on the consideration that Waepandan Village is coconut production center area. Respondents in this research as many as 30 respondents who do copra processing. Determination of respondents conducted by Random Sampling Method. The data analysis used is value-added analysis (Hayami Method). The results showed that the processing of copra provides added value of Rp. 2,149.4/kg ratio of value added to product value  of  41.74%